Ischaemic Heart Disease: Accuracy of the Prehospital Diagnosis—A Retrospective Study - Louise Houlberg Hansen; Søren Mikkelsen (Emergency Medicine International)
Purpose. Correct prehospital diagnosis of ischaemic heart disease (IHD) may accelerate and improve the treatment. We sought to evaluate the accuracy of prehospital diagnoses of ischemic heart diseases assigned by physicians. Methods. The Mobile Emergency Care Unit (MECU) in Odense, Denmark, services a population of 260.000. All admissions in 2009 concerning patients diagnosed in the IHD category were assessed. Outcome and diagnosis of each patient were manually validated in accordance to the final diagnosis established following admission to hospital, using the discharge summary from the relevant department as reference. Results. 428 MECU runs with a prehospital diagnosis of IHD were registered. 422 of these were included in the study and 354 of those patients were suitable for this analysis. 73,4% of the patients hospitalized with a prehospital diagnosis of IHD were initially admitted to the relevant ward. Of these patients, 40,0% had their preliminary diagnosis of IHD confirmed. 14,1% of all patients admitted to the hospital were diagnosed with nonheart conditions. Preliminary diagnoses of STEMI had an accuracy of 87,5%. Conclusions. The preliminary IHD diagnoses assigned by the MECU physicians were acceptable. In case of STEMI patients the diagnostic accuracy was excellent. In this study there was an apparent overtriage.